Tax Enforcement Procedure Under Section 104 of Personal Income Tax Act: Matters Arisings - John, Kachi Bielu (Journal of Legal Studies, 2020)
The refusal of a taxpayer to respond or pay the tax due has always provoked the tax authority to approach the court with an ex-parte application in chambers. The result of this ex parte application arms the tax authority with a restraining order. With a detached team of policemen, the tax authority will storm the premises of the taxpayer, vandalize, forcefully drive out the tax payer and seal up the premises. All these arrangements and decisions are done behind the taxpayer. This paper examined the constitutionality of the entire procedure for the recovery of tax due to the tax payer. The paper utilized doctrinal methodology in analyzing the extant laws and case laws as they relate to the subject matter. The paper submits that decisions under section 104 PITA are too weighty to be taken in the absence of the taxpayer. The paper, therefore, recommends some sort of judicial activism by judicial officers in exercising their discretion and accommodate the interest of the taxpayer.